THE IMPORTANCE OF CORPUS LINGUISTICS IN ANALYSIS OF ECONOMIC TEXTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the importance of the achievements of corpus linguistics in the analysis of economic texts. The author considers the possibilities of studying various language materials in the economic field using automated methods. In particular, using the methods of corpus linguistics, the frequency of use and contextual features of economic terms, language units are studied. At the same time, the practice of creating a corpus of sectoral texts and analyzing them is also covered. This approach serves to provide a deep understanding of trends in economic language and to improve effective translation, editing and teaching processes.